Electrochemistry: general aspects - Zagal-Moya, J; Zagal-Moya, J (Elsevier, 2025)
This chapter is a brief introduction to electrochemistry, organic electrochemistry and electrode kinetics. It covers the main aspects of electrode kinetics with emphasis on differentiating between outer and inner sphere redox process, with a brief introduction to Marcu’s theory for single one electron transfer, the Butler–Vomer equation and inner sphere multiple electron transfer processes generally involved in organic electrochemistry and catalytic systems. A brief overview of some chapters of the book is also included. Finally, organic electrochemistry is expanding so widely that it is practically impossible to include all different fields in one single book, and it is an invitation to open new frontiers in this field. © 2026 Elsevier Inc. All rights reserved.